Developer Perception and Interest in Solar Power Plant Investment: Case Study To Encourage Clean Energy Investment - Muh Zuhdi Irwansyah; Zuliani Dalimunthe (Green Publisher Indonesia, 2025)
Despite Indonesia’s vast solar energy potential and supportive regulatory frameworks, private sector investment in solar power plants remains limited. This study aims to explore developer perceptions and investment interest in the solar power plant sector and identify key factors influencing their decision-making. Employing a qualitative case study approach, data were collected through in-depth interviews with developers experienced in both fossil-based and renewable energy projects. Thematic analysis reveals that consistent regulation, revenue certainty through Power Purchase Agreements (PPAs), and land availability are critical drivers of investment interest. Additionally, perceived regulatory risks, cost of capital, and local policy requirements such as domestic content obligations shape developers’ strategies toward solar project participation. This study contributes to the literature by offering developer-centered insights on investment behavior in emerging renewable markets.